Imagining alternative paths for WHO 75 years in - Birn, A.E.; Kumar, R.; Arteaga-Cruz, E.; Twala, B.; Baduza, M. (Elsevier, 2023)
WHO's 75th anniversary comes at a fraught moment. The vaccine apartheid that has marked the COVID-19 pandemic response has once again raised questions about the influence of corporate actors and their Global North partners on global health. Amid perennial debates around reform and mounting calls for decolonising global health and interrogation of who is represented by WHO, we highlight a set of missed opportunities from the past and offer reimaginings of how WHO might propitiously forge a path towards its centenary in a more equitable, representative, and counter-hegemonic way. We introduce possibilities of centring the needs, priorities, and agency of Global South, public-interest civil society organisations (CSOs), social movements, and Indigenous peoples in this agenda. WHO's early years were marked by prospects of integrating social medicine—addressing health as produced by social conditions and unequal power relations—and tensions over decolonisation and asymmetrical decision making. WHO's first Director-General was the Canadian psychiatrist Brock Chisholm, who favoured social medicine approaches over top-down technical disease campaigns, typified by the Rockefeller Foundation's activities and backed by the US-led bloc. However Chisholm, an avowed opponent of Cold War rivalries playing out at WHO, refrained from defying the USA or mobilising member states from the Global South, and stepped down after one term. Subsequently, disease campaigns became WHO's signature approach, ranging from efforts against yaws and tuberculosis to malaria and smallpox campaigns that amped up during the 20-year directorship of Brazilian physician Marcolino Candau, a former Rockefeller Foundation officer. WHO's sidelining of social medicine, in all its complexity, was an early missed opportunity. WHO was also mired in ongoing paternalism and colonialism. Global South members complained that their experts were overlooked as advisers and staff, even as financing obligations burgeoned. Citing aid levels incommensurate with dues levied and postwar rebuilding needs, the Soviet Union and Eastern bloc members withdrew from UN agencies from 1949 to the mid-1950s. Many Latin American countries sympathised with this action, but were not in a position to leave WHO or challenge top-down approaches on their own. During this period European powers sought to constrain the UN's and WHO's partial efforts to address colonial conditions. French authorities claimed to uphold the UN Charter, yet resisted decolonisation and accused WHO of harbouring “anti-colonial” attitudes. WHO's African Regional Office (AFRO), relocated from London, UK, to what was “French” Equatorial Africa by 1954, was headed by a Portuguese tropical medicine doctor until 1964. AFRO continued to hold European-chaired meetings in such colonial strongholds as Luanda in then “Portuguese” Angola, reflecting ongoing colonial paternalism. Arguably, WHO is still disentangling itself from this legacy. WHO heeded the UN's unprecedented 1962 denunciation of apartheid, stripping South Africa of its voting rights, but what if WHO had condemned imperialism and racism outright, enabling a decolonised approach to leadership and agenda setting decades earlier? A previous declaration by the Soviet Union in 1961 that called for WHO to “help elimina[ate] the consequences of colonialism” in health garnered wide backing from African and socialist countries. Meeting opposition from Global North countries, notably the UK, the World Health Assembly (WHA) shelved this proposal, and showed little support for the non-aligned movement's pro-sovereignty and trade justice agendas. Two decades later the 1978 Alma-Ata primary health care (PHC) conference served as a propitious, if imperfect, launching pad to address some of the needs and demands of the Global South. The Alma-Ata Declaration and its Health for All pledge underscored the centrality of communities in building PHC and called for intersectoralism, with PHC framed in language of social justice, even decrying “existing gross inequality” in people's health between (and within) countries as being “politically, socially and economically unacceptable”. With WHO's third Director-General, Danish physician Halfdan Mahler, thwarted by Cold War tensions, the Alma-Ata Declaration steered clear of endorsing national health services and free health care; nonetheless, its espousal of community-driven, bottom-up PHC efforts spawned several path-breaking PHC models in Global South settings. But WHO's PHC plans were shortly disrupted by the Rockefeller Foundation's Selective Primary Health Care (SPHC) strategy, portrayed as more practical. By 1984 SPHC was crystallised in UNICEF's “Child Survival Revolution”, heralding four low-cost interventions (growth monitoring, oral rehydration therapy, breastfeeding, and immunisation). Given Rockefeller Foundation, World Bank, and UNDP co-sponsorship, plus massive US funding, WHO jumped on the bandwagon. But what if WHO had resisted SPHC, as many staff and health advocates demanded? Might this have enabled sustained commitment to comprehensive PHC? Certainly, WHO's agenda-setting autonomy diminished after the USA slashed its assessed contributions to WHO and the WHA froze member states’ dues, amid rising neoliberalism. This was partly motivated by industry pressure after WHO's advocacy for generic medicines and joint Code of Marketing of Breast-milk Substitutes with UNICEF, a highlight of WHO challenging of corporate influence, followed later by its Framework Convention on Tobacco Control. Thereafter, WHO became reliant on ear-marked budget contributions from member states, private foundations, the World Bank, and other actors: these rose from 20% in the 1970s to over 80% in 2022, substantially compromising WHO's independence. By the 1990s WHO resistance to corporate influence diminished as the World Bank consolidated its health and development purview after the Soviet Union's dissolution. The World Bank's 1993 “investing in health” approach was influential; it advocated private insurance and delivery alongside public financing of a nationally defined package of essential services. WHO's official position on private sector involvement in health remained ambiguous, only treading lightly on privatisation trends amid equity concerns. WHO's budget shortfalls were now being partly met via public–private partnerships, ushering in the private sector to shape decision making and enabling private actors to access and leverage sizable government resources. In 1999, WHO Director-General Gro Harlem Brundtland, a former Prime Minister of Norway, welcomed non-governmental organisations and the private sector as partners in the fight against poverty and disease. The new Bill & Melinda Gates Foundation became a key global health agenda-shaper via large-scale support for organisations such as Gavi, the Vaccine Alliance and the Global Fund to Fight AIDS, Tuberculosis and Malaria and as a key WHO donor to earmarked programmes, including polio eradication. The next decade saw WHO pursuing seemingly contradictory efforts. WHO's 2005–08 Commission on Social Determinants of Health declared that “social injustice is killing people on a grand scale” and called for “tackl[ing] the inequitable distribution of power, money and resources”, as well as a single tier of health care financed through general taxation or mandatory insurance. Sidestepping this agenda, WHO accepted public–private oriented universal health coverage as a fix for health-care systems. Here was another missed occasion for WHO to emphasise the crucial role that governments play in health—vividly illustrated in various Global South settings that have made progress in advancing health equity. Instead, WHO remained evasive and the 2010 World Health Report advocated for governments to steward both public and private sectors and “constructively engage” with the latter. This approach continued in subsequent years. The stark vaccine inequity and apartheid that occurred during the COVID-19 pandemic visibilised WHO's limited political authority and independence. Under its normative function, WHO provided medical and technical guidance, coordinated country responses, and co-founded COVAX, which sought to accelerate vaccine development and production, and “guarantee fair and equitable access for every country in the world”. However, by January, 2023, only a quarter of African residents had received two vaccine doses. With a meagre target of vaccinating 20% of the global population, COVAX was largely shaped by philanthro-capitalist and corporate actors, rather than supporting patent-free distribution. Meanwhile, Global North countries made bilateral agreements with vaccine manufacturers independently of COVAX to secure vaccines. Such dealings constrained WHO's efforts to respond in a socially just and equitable way to the pandemic. The Global North hoarded vaccines and some of its most powerful governments blocked, repeatedly delayed, and watered down a Trade-Related Aspects of Intellectual Property Rights waiver proposal, co-sponsored by 65 countries, to suspend patent protections for COVID-19 technologies for the duration of the pandemic. This contributed to avoidable deaths across the Global South. This was hardly the first time that WHO's promise and pitfalls were revealed. WHO's initial response to HIV/AIDS was belated and inadequate, yet it yielded to self-correction and redirection. A key strategy involved identifying marginalised groups as protagonists in improving prevention, detection, and treatment of HIV/AIDS. Across multiple struggles, CSOs already knew that the best health response is to prioritise the most vulnerable while empowering them to lead on their care. For example, the work of the Treatment Action Campaign, the AIDS Law Project, and partners helped propel WHO's support for access to medicines, thanks to public education, campaigning, and litigation, accompanied by sustained advocacy. The right to access antiretroviral treatment in South Africa, and forcing pharmaceutical companies to reduce exorbitant prices, were won on the streets through mass mobilisation. At WHO, the 3-by-5 campaign (ensuring access to antiretroviral treatment for 3 million people by 2005) was adopted during the short tenure of South Korean Lee Jong-wook as Director-General. Realised in 2007, this ambitious effort raised WHO's profile in HIV/AIDS. Building relationships with CSOs and social movements sooner would have accelerated WHO's ability to influence public perceptions about HIV/AIDS; still, its turnaround marked a crucial shift in advancing HIV treatment for all. Under the leadership of WHO's first African Director-General, Tedros Adhanom Ghebreyesus, WHO has given more focus to the Global South and initiated an mRNA vaccine technology transfer hub based in South Africa and a draft pandemic treaty. Both initiatives seek to empower “lower-income countries” to produce medicines domestically and impel all countries to share knowledge in preparation for future pandemics. However, a pandemic treaty will only be transformative if guided by never-again values: never again should profiteering come at the expense of health and equity; never again should corporations and Global North hoarders guide distribution of life-saving therapeutics. Whether WHO's encouraging work on commercial determinants will help rein in the structural factors enabling systemic corporate impunity remains a question. To make progress, WHO will need backing from Global South leaders and health ministries, alongside support from CSOs, social movements, community-based organisations, and youth. Young people have already wielded their collective voice and activism to counteract climate denialism and hold governments accountable for their inaction on the climate crisis. Imagine their potential to recapture WHO's agenda for future generations. Health for All implies not only tackling inequalities in health but also addressing our relationship with the Earth. To tackle health inequalities, we must first acknowledge that they are produced and reproduced by relations of production and social reproduction. To be sure, this has implications for WHO's conceptualisation of and approaches to health; it also demands a reimagining of who truly constitutes WHO. Indeed, with WHO at the fulcrum, global health governance to advance equity might be imagined in other creative ways that centre the health and wellbeing of the world's made-marginalised groups, including Indigenous peoples. After all, in Latin America, as elsewhere in the Global South, “liberated” nation states were only fictionally free from colonisation. Some newly “independent” states heeded liberal principles of individual rights and equality; however, Indigenous peoples were neither recognised as free citizens until well into the 20th century, nor were they voluntarily bound by these political arrangements. Moreover, their collective rights were erased. The struggle of the Indigenous movement in Ecuador engendered an alternative proposal, plurinationality, inscribed in the country's 2008 Constitution. Plurinationality radically questions the validity of nation states that systematically ignore diversity, and calls for recognition of collective rights and the vindication of community self-governance and Indigenous ways of living. Because Indigenous peoples have been largely excluded from citizenship in many settings, their needs and priorities have rarely been represented at WHO. One path-breaking imagining would be for WHO to recognise Indigenous nations and regional Indigenous organisations as valid voices with voting rights and representation at its decision-making bodies. Ensuring that all other made-marginalised groups—such as Palestinians, Black diasporic descendants of enslaved Africans, women in patriarchal societies, and people with disabilities—are justly represented at WHO is essential to its ability to fulfil its mission and thrive into the future. Partner to this reimagining is centring the rights of nature, not simply as resources for humans but as inherently sacred. For example, the understanding of water as life in Aotearoa/New Zealand has culminated in the Te Awa Tupua (Whanganui River Claims Settlement) Act (2017), which recognises jurisdictional rights for the spirit that protects water as an element of colonial reparation for Māori people. Acknowledging ill health as inextricably linked to power asymmetries and environmental plunder within the global capitalist order, we might imagine radical new futures. Why not envision a WHO that upholds the rights of nature and prior informed consent in Indigenous and Global South regions? Why not a health governance body charged with alerting publics of the health harms of International Monetary Fund-led austerity programmes, unfair trade dispute terms, or extractive capitalism? And why not dream of a WHO that champions health as a collective right of people based on nature as protected instead of captive to corporate interests? Reimagining a WHO for all peoples, including those who have historically been excluded, murdered, or sacrificed in zones of extraction, is possible.